Penerapan Electronic Traffic Law Enforcement (Etle) Terhadap Tindak Pidana Pelanggaran Lalu Lintas - Mochamad Fridho Ardyansyah; Noenik Soekorini; Sri Astutik (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
The development of information technology has driven a transformation in the law enforcement system, including in the field of traffic through the implementation of Electronic Traffic Law Enforcement (ETLE). This study aims to analyze the legal provisions of ETLE and sanctions for traffic violations from a positive legal perspective in Indonesia. The method used is normative juridical with a statutory and conceptual approach. The results show that ETLE has a strong legal basis in the Traffic and Road Transportation Law and the Electronic Information and Transactions Law. However, its implementation has not been optimal due to factors such as public awareness, limited infrastructure, and coordination between institutions. Therefore, strengthening technical regulations, increasing public legal literacy, and developing a more integrated technology-based system are needed.